Recurrent hypocalcemia due to postoperative total thyroidectomy: a case report - Wibawa, I. Dewa Gede Amara Putra; Wulandari , Dewi Catur (International Journal of Advances in Medicine, 2024)
Hypocalcemia is a common complication following total thyroidectomy, caused by inadvertent damage or removal of the parathyroid glands responsible for calcium regulation. This condition poses a significant challenge in postoperative management, often leading to symptoms such as carpopedal spasm, convulsion, and airway constriction occur during hypocalcemia. Patients undergoing total thyroidectomy require vigilant monitoring of serum calcium levels, especially in the immediate postoperative period. Treatment typically involves calcium to prevent hypocalcemic episodes. Long-term management strategies may include the use of calcitriol. We report 30-years-old Indonesian woman suffer hypoparathyroidism because postoperative total thyroidectomy. For a month she did not have any complaints after being prescribed calcium supplement and levothyroxine. But she has stopped the calcium supplement and levothyroxine for 2 days, then she went to emergency room with stiffness all part of body. This report describes proper education of patients on recognizing symptoms of hypocalcemia and ensuring regular follow-up care are essential to prevent complications and improve quality of life post-thyroidectomy.